A Study of the Efficacy and Safety of Aerobic Exercise Training in Pulmonary Arterial Hypertension (the Saturday Study): Protocol for a Prospective, Randomized, and Controlled Trial - Jiang, Rong; Wang, Lan; Yuan, Ping; Zhao, Qin-Hua; Gong, Su-Gang; He, Jing; Qiu, Hong-Ling; Luo, Ci-Jun; Zhang, Rui; Shen, Ting; Zhan, Meng-Yi; Jiang, Yu-Mei; et al. (Frontiers in Medicine, 2022)
Background Patients with pulmonary arterial hypertension (PAH) have reduced exercise capacity and poor quality of life. Exercise-based rehabilitation in PAH results in clinically relevant improvements in exercise capacity and hemodynamics. To clarify the mechanism, we will evaluate the effect of aerobic exercise training rehabilitation on right ventricular (RV) remodeling and function as determined measured by cardiac magnetic resonance imaging (CMR). Methods We will conduct a 26-week multicenter randomized controlled trial. Patients on stable and unchanged PAH-targeted medication are randomly assigned (1:1) to the control and training groups. The primary endpoint is the RV stroke volume (RVSV) change from baseline to Week 26, determined by CMR. Comprehensive RV function is also performed using CMR. Other characteristics of the RV and left ventricle, World Health Organization functional class, 6-min walk distance, and N-terminal pro-B-type natriuretic peptide are included in secondary endpoints. We also investigate the proteomic, metabolomic, and transcriptomic changes after exercise training as exploratory endpoints. Ethics and Dissemination The study and protocol were approved by the Ethics Committee of Shanghai Pulmonary Hospital (Approved No. of ethics committee: L20-17). The results will be disseminated at medical conferences and in journal publications. All participants will sign written informed consent. Trial Registration Number ChiCTR2000031650.